EFFECT OF GRAIN FLOUR SUBSTRATE SUPPLEMENTS ON THE PRODUCTIVITY OF PLEUROTUS FLORIDA (Journal of Plant Disease Sciences, 2017)
Seven grain (pulses and cereals) flours were evaluated (each @ 5% of wet weight of substrate) as supplements to the wheat straw used for cultivation of the oyster mushroom . All the test supplements influenced the Pleurotus florida vegetative and reproductive growth phases, yield contributing traits and fresh fruiting body yield of , over untreated control. Pigeonpea, Chickpea, P. florida Pearlmillet and Sorghum grain flours recorded minimum days to spawn run (13-15 days), pinhead initiation (17-19 days) and development of matured fruiting bodies (20-22 days), as against 18, 21 and 24 days, respectively in untreated control. All the supplements enhanced the average number of pinheads and matured fruiting bodies /bed, average diameter of pileus and stipe and stipe length. There were about 24 to 32 and 6 to 30 percent increase, in per bed average number of pinheads and matured fruiting bodies, about 6 to 28 and 10 to 29 per cent increase in average diameter of pileus and stipe, respectively, and stipe length (6 to 27 %); over untreated control. All the test supplements recorded higher fresh mushroom yield in the range of 1269.52 g to 1412.00 g /bed (each bed of 1.5 kg dry substrate) with biological efficacy in the range of 82.81 to 94.46 per cent, as against 1116.45 g /bed yield and 74.42 percent biological efficiency in untreated control. Thus, it can be concluded that supplementation of the basic substrate with the flour of pulse / cereal grains certainly improve the yield and yield contributing traits of . Pleurotus florida
Keywords: supplements, cereal, pulses, flour, yield Pleurotus florida